PERSEPSI KARYAWAN TERHADAP PENGGUNAAN TEKNOLOGI INFORMASI DALAM SISTEM INFORMASI AKUNTANSI (Studi Empiris di Rumah Sakit Permata Grup) - Iwan Koerniawan; Henny Henny (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2018)
Abstract This study aims to determine employee perceptions about the use of information technology in accounting information systems at the Permata Group Hospital by using the theory of Technology Acceptance Model. The use of TAM model is based on the fact that so far TAM is a concept that is considered the best in explaining the behavior of the user of new information technology systems . The population in this study were all employees the Accounting and Finance at the Permata Group Hospital which includes Permata Bunda Hospital in Purwodadi and Permata Medika Hospital in Semarang. Sampling was conducted using population census, that is 32 people .These results prove the hypothesis is accepted 4 of total 5 proposed hypothesis Relationships proved significant : a) the effect of perceived ease of use (PEOU) on perceived usefulness (PU) , b ) the effect of perceived ease of use (PEOU) of the attitude toward using (ATT) , c ) the effect of perceived usefulness (PU) of the acceptance of information technology (ACIT) , and d ) the effect of attitude toward using (ATT) on the acceptance of information technology (ACIT) . This proves that the employees' perception of the use of information technology in accounting information systems based on information technology can be explained by the theory of Technology Acceptance Model (TAM)